2014
DOI: 10.5021/ad.2014.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Bone Marrow-Derived Mesenchymal Stem Cells and Platelet-Rich Plasma in Streptozotocin-Induced Diabetic Rats

Abstract: BackgroundDiabetic wounds are a major clinical challenge, because minor skin wounds can lead to chronic, unhealed ulcers and ultimately result in infection, gangrene, or even amputation. Studies on bone marrow derived mesenchymal stem cells (BMSCs) and a series of growth factors have revealed their many benefits for wound healing and regeneration. Platelet-rich plasma (PRP) may improve the environment for BMSC development and differentiation. However, whether combined use of BMSCs and PRP may be more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 29 publications
6
30
0
2
Order By: Relevance
“…It is expected that microenvironmental of hBM-MSCs may improve trans-differentiation this type of cell into insulinproduced β-cells. There are data that platelet-rich plasma might be useful for increasing of differentiation capacity of the hBM-MSCs [34] . Moreover, it has been postulated that hBM-MSCs probably would be considered more optimal candidates for further clinical implementation when compared with induced PSC, while this predisposition is required strong and continuous investigations.…”
Section: Regeneration Of β Cell Mass and Restoring Of Functional Propmentioning
confidence: 99%
“…It is expected that microenvironmental of hBM-MSCs may improve trans-differentiation this type of cell into insulinproduced β-cells. There are data that platelet-rich plasma might be useful for increasing of differentiation capacity of the hBM-MSCs [34] . Moreover, it has been postulated that hBM-MSCs probably would be considered more optimal candidates for further clinical implementation when compared with induced PSC, while this predisposition is required strong and continuous investigations.…”
Section: Regeneration Of β Cell Mass and Restoring Of Functional Propmentioning
confidence: 99%
“…These proteins regulate cell migration and proliferation (mitogenesis), remodel the extracellular matrix, and promote angiogenesis, creating a favourable environment that quickly stimulates tissue repair and wound healing. 13,14 Various studies on the complications of diabetes mellitus have demonstrated extensive alterations to bone and mineral metabolism, causing diabetic osteopenia. Some of the factors that have been associated with the pathogenesis of this bone disorder include hyperglycaemia, oxidative stress, and body weight loss.…”
mentioning
confidence: 99%
“…Increasing stem cell potency with adjuvants such as platelet-rich plasma or Panax notoginseng saponins are possible alternatives for decreasing the minimum required dose. 95,96 Means of prolonging transplanted cell lifespan are now heavily sought, as MSCs must survive to influence healing. Numerous possibilities have arisen, such as hyperoxic and pan-caspase pretreatment, which reduces MSC apoptosis in ischemic microenvironments.…”
Section: Improving Stem Cell Yield Efficacy and Lifespan -Current Amentioning
confidence: 99%